ANALISIS PENGARUH TENAGA KERJA, MODAL, HARGA, DAN TEKNOLOGI TERHADAP PENDAPATAN UMKM DI KOTA DENPASAR - Sintiawati, Ni Putu Ayu; Purbhadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including expanding employment opportunities, playing a role in equity and increasing people's income, and can contribute to economic recovery due to the crisis. Therefore it is necessary to know what factors influence MSME income so that they can make a more optimal contribution to the Indonesian economy. The purpose of this study is to analyze the variables of labor, capital, prices, and technology simultaneously which have a significant effect on the income of MSMEs in Denpasar City and to analyze the variables of labor, capital, prices, and technology partially which have a positive and significant effect on the income of MSMEs in the City of Denpasar. Denpasar. This research uses a quantitative approach in the form of associative. The analysis technique in this study uses multiple linear regression analysis techniques. The results of this study found that simultaneously the variables of labor, capital, prices, and technology had a significant effect on the income of MSMEs in Denpasar City. The variables of labor, capital, price, and technology partially have a positive and significant effect on the income of MSMEs in Denpasar City.